2015
DOI: 10.3390/w7105525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal Thermal Stratification on the Functional Diversity and Composition of the Microbial Community in a Drinking Water Reservoir

Abstract: Abstract:The microbial communities within reservoir ecosystems are shaped by water quality and hydrological characteristics. However, there are few studies focused on the effects of thermal stratification on the bacterial community diversity in drinking water reservoirs. In this study, we collected water samples from the Jinpen Reservoir around the re-stratification period. To explore the functional diversity and bacterial community composition, we used the Biolog method and 16S rRNA-based 454 pyrosequencing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 62 publications
2
32
0
1
Order By: Relevance
“…Furthermore, trends of physicochemical factors were mainly consistent across all four depths, with the exception of turbidity. It was revealed that the spatial variation of all water quality parameters from October to December in Jinpen reservoir was not significant, resulting from Jinpen reservoir being in a mixed state during that period, with a similar vertical stratification of its physical and chemical factors [50]. Recently, Zhou et al [51] conducted field research onthe impact of a water-lifting aeration system on water quality and microbial community structure in a drinking water reservoir, and found that reservoir stratification was successfully eliminated due to the artificial mixing, which strongly affected environmental variables and obviously diminished differences of water quality between the bottom and surface.…”
Section: Variation Of Water Quality Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, trends of physicochemical factors were mainly consistent across all four depths, with the exception of turbidity. It was revealed that the spatial variation of all water quality parameters from October to December in Jinpen reservoir was not significant, resulting from Jinpen reservoir being in a mixed state during that period, with a similar vertical stratification of its physical and chemical factors [50]. Recently, Zhou et al [51] conducted field research onthe impact of a water-lifting aeration system on water quality and microbial community structure in a drinking water reservoir, and found that reservoir stratification was successfully eliminated due to the artificial mixing, which strongly affected environmental variables and obviously diminished differences of water quality between the bottom and surface.…”
Section: Variation Of Water Quality Parametersmentioning
confidence: 98%
“…Overall, Chao 1 indices were lowest in October and highest from November to December, ranging from 143 to 476. Moreover, the Chao 1 richness index was higher than the OTU value, indicating that more unidentified sequences are still to be studied in the reservoir [50]. Variations of Shannon diversity (H') were analogous to the Chao 1 index.…”
Section: Microbial Eukaryotic Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested a great and conserved diversity at the study sites. Recent studies in a water reservoir in China (Yang;Huang;Zhang, 2015) showed the effect of thermal stratification on bacterial communities. The authors explored the functional diversity and bacterial community composition using the Biolog method and 16S rRNA-based 454 pyrosequencing.…”
Section: Microbial Metabolic Profilementioning
confidence: 99%
“…The sediment microbial community has drawn great attention from microbial ecologists [18][19][20][21]. Moreover, the sediment host distinct microbial communities and their populations may strongly be affected by the nutritional status of water quality due to the variations of hydrological regime and other physical and chemical variables, including hydrostatic pressure [22][23][24][25].…”
mentioning
confidence: 99%